Réponses

2014-09-05T17:14:10+02:00
1)a) x²-3 est déjà sous forme canonique.
b) x²-3=(x+√3)(x-√3)
c) (x+√3)(x-√3)=0
⇔x+√3=0 ou x-√3=0
⇔x=-√3 ou x=√3

2)a) x²-x-1=x²-2*1/2*x+1/4-1/4-1
x²-x-1=(x-1/2)²-5/4
b) (x-1/2)²-5/4=(x-1/2+√5/2)(x-1/2-√5/2)=(x-(1-√5)/2)(x-(1+√5)/2)
c) (x-(1-√5)/2)(x-(1+√5)/2)=0
⇔x-(1-√5)/2=0 ou x-(1+√5)/2=0
⇔x=(1-√5)/2 ou x=(1+√5)/2

3a) 2x²-12x+13=2(x²-6x+13/2)
2x²-12x+13=2(x²-2*3*x+9-9+13/2)=2((x-3)²-5/2)
b) 2x²-12x+13=2(x-3+√5/√2)(x-3-√5/√2)
c) 2(x-3+√5/√2)(x-3-√5/√2)=0
⇔x-3+√5/√2=0 ou x-3-√5/√2=0
⇔x=3-√5/√2 ou x=3+√5/√2

4)a) -x²+x+15/4=-(x²-x-15/4)
-x²+x+15/4=-(x²-x+1/4-1/4-15/4)=-((x-1/2)²-4)
b) -x²+x+15/4=-(x-1/2+2)(x-1/2-2)=-(x+3/2)(x-5/2)
c) -x²+x+15/4=0
⇔-(x+3/2)(x-5/2)=0
⇔x+3/2=0 ou x-5/2=0
⇔x=-3/2 ou x=5/2








Merci infiniment mais je ne comprend pas le 3a